2020
DOI: 10.3390/ani10010094
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Glucocorticoid Metabolites and H/L Ratio Are Related Markers of Stress in Semi-Captive Asian Timber Elephants

Abstract: Animals are kept in captivity for various reasons, but species with a slower pace of life may adapt to captive environments less easily, leading to welfare concerns and the need to assess stress reliably in order to develop effective interventions. Our aim was to assess welfare of semi-captive timber elephants from Myanmar by investigating the relationship between two physiological markers of stress commonly used as proxies for welfare, faecal glucocorticoid metabolite concentrations (FGM) and heterophil/lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
5
6
0
Order By: Relevance
“…For fGCMs, relationships with age are not always clear. In this study, there was no age effect, which was comparable to a study of semicaptive elephants in Myanmar [97]. However, a study of tourist camp elephants in Thailand found older animals exhibited overall lower fGCM concentrations [98].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For fGCMs, relationships with age are not always clear. In this study, there was no age effect, which was comparable to a study of semicaptive elephants in Myanmar [97]. However, a study of tourist camp elephants in Thailand found older animals exhibited overall lower fGCM concentrations [98].…”
Section: Discussionsupporting
confidence: 84%
“…However, a study of tourist camp elephants in Thailand found older animals exhibited overall lower fGCM concentrations [98]. One reason might be how age groups were defined, being across four broad age categories in this study and that of Seltmann et al [97] compared to using age as a continuous variable in Bansiddhi et al [98]. In terms of sex effects, those results have also not always been consistent, even in the same population.…”
Section: Discussionmentioning
confidence: 56%
“…Behavioral observation and physiological indicators were elaborated in this research. In line with other researches (Davis et al 2008;Seltmann et al 2020), this present research showed that the N/L ratio could be used as a physiological stress indicator in the field or remote area. Behavior observation was merely enough to measure stress response (Hofer and East 1998).…”
Section: The Correlation Between Stereotypic Behavior and Physiologic...supporting
confidence: 91%
“…Each neutrophil and lymphocyte were counted within 200 white blood cells under the microscope (Kerr 2002;Theml et al 2004;Shiravastav et al 2012). Then the counted neutrophils were manually divided by counted leucocytes to obtain the N/L ratio (Dhabhar et al 1996;Stockman et al 2011;Seltmann et al 2020).…”
Section: Neutrophil/lymphocyte Ratio (N/l Ratio) Countmentioning
confidence: 99%
See 1 more Smart Citation